PERSPEKTIF AKUNTANSJ ATAS ASET PENGETAHUAN (KNOWLEDGE ASSET) - Widyaningdyah, Agnes Utari (Widya Mandala Surabaya Catholic University, 2009)
Today s economies shifted the dynamic business environment into information age where people interact with knowledge. In this new economy, knowledge management and intellectual capital are emerging as the p